2020
DOI: 10.1002/ceas.12170
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Evaluation of the Intersectional Privilege Screening Inventory for Use With Counselors‐in‐Training

Abstract: As counselor preparation programs are compelled to demonstrate student social and cultural competence, valid inventories are needed to measure development consistent with contemporary standards. The Intersectional Privilege Screening Inventory was created for this purpose, was assessed using 4 types of validity evidence, and has results supporting its use in student development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…Within transformative learning, educators engage in a participatory process of constructing meaning while questioning and reframing unconscious attitudes and values (Baumgartner, 2001). Researchers have found that counselor multicultural and social justice competency begins with a process of self-reflection and identification of positions and biases (Black & Stone, 2005; Pester et al, 2020; Ratts et al, 2016). We describe activities that facilitate educator examination of implicit bias, privilege, microaggressions, and coconspiratorship; this examination starts with cultural proficiency and may be different for individuals from nondominant and dominant cultures.…”
Section: An Evidence-based Antiracist Approach To Multitiered Systems...mentioning
confidence: 99%
“…Within transformative learning, educators engage in a participatory process of constructing meaning while questioning and reframing unconscious attitudes and values (Baumgartner, 2001). Researchers have found that counselor multicultural and social justice competency begins with a process of self-reflection and identification of positions and biases (Black & Stone, 2005; Pester et al, 2020; Ratts et al, 2016). We describe activities that facilitate educator examination of implicit bias, privilege, microaggressions, and coconspiratorship; this examination starts with cultural proficiency and may be different for individuals from nondominant and dominant cultures.…”
Section: An Evidence-based Antiracist Approach To Multitiered Systems...mentioning
confidence: 99%
“…We provided reviewers with a clear description of the items and requested qualitative feedback regarding the items’ clarity, the items’ relevance within the identified domain, and the thoroughness of items including any suggestions regarding potentially missing content. We also asked reviewers to rate each item as essential; useful, but not essential; or not necessary (Pester et al, 2020). We offered participants a $50.00 Amazon gift card incentive to compensate them for their time and expertise in providing a quality review.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Gonzalez-Voller et al encouraged counselors to remain aware of contemporaneous community and global issues affecting individuals of various intersecting identities. Although the historical context and relevance of multicultural and social justice counseling are important, counselors and CITs need more resources to help examine personal positions of privilege embedded within the intersectional framework of the MSJCC (Pester et al, 2020).…”
Section: Intersectional Privilege In Counselor Developmentmentioning
confidence: 99%
“…The MSJCC support the high emphasis placed on understanding the effects of power and privilege as a critical element of understanding multicultural and social justice in counselor preparation and training (Council for the Accreditation of Counselor and Related Education Programs [CACREP], 2015, Standards 2.F.2.b., 2.F.2.e., and 2.F.2.h). Yet, despite the proliferation of the MSJCC, few instruments yielding psychometrically validated scores exist for gauging a counselor's own intersecting identities and positions of privilege in educational or professional counseling contexts (Chan et al., 2018; Hays, 2020; Pester et al., 2020).…”
Section: Introductionmentioning
confidence: 99%